Knowledge, Attitude, and Practice of Breast-Self Examination Among Female Students of Niger Delta University - Deborah Oboli; Oluchi Mkpae; Monica Anurika Gbuchie; Tonte Gbuchie (International Journal of Medical Students)
BACKGROUND: Cancer, characterized by uncontrollable cell division leading to tissue destruction, is a leading cause of death globally. Breast cancer, in particular, affects 2.1 million women annually and causes significant mortality, especially in less developed regions due to late detection and limited access to treatment. In Nigeria, the incidence rate of breast cancer is 33.6 per 100,000 women. Early detection through methods like breast self-examination (BSE) is crucial, particularly in developing countries where mammography may not be feasible. BSE is recommended due to its simplicity, privacy, and lack of cost, yet awareness and practice remain low. This study assesses the knowledge, attitude, and practice of BSE among female students at Niger Delta University to provide insights into the effectiveness of current awareness efforts.